Idol of Ganapati at the shores of Khar Danda - Mumbai Archive Project Team (Jio Institute, 2024)
Before setting out to sea, fishermen visit the Ganapati shrine to offer prayers. In 2004, this offshore platform was built on top of a naturally occurring rock formation.